Relationships Between Shadow Economy and Foreign Direct Investment, Growth and Poverty - Deilami, Hesam Nikopour (2010)
Economic activities may be classified under a structural approach into two major group namely formal economy and shadow economy. On a broad aspect, shadow economy encompasses the operations not taken to national accounts. Omission of some economic operations from national accounts may create numerous problems in policy making. Until recently, quantitative analyses of relationship between shadow economy and other economic variables across countries were not possible due to lack of shadow economy data. Fortunately, the recent availability of its data, in particular Schneider et al. (2010) estimates of the shadow economy as percentage of official GDP makes such an issue researchable. This study investigates the theoretical issues and empirical evidences related to 1) shadow economy and foreign direct investment, 2) shadow economy and economic growth, and 3) shadow economy and poverty. In most of the studies on possible causes of the shadow economy, tax burden is considered nationally and the effect of tax avoidance in a global scale is not mentioned. The first objective of this study is to investigate the causal relationship between FDI and the shadow economy using causality methods GMM estimator, based on observations for a sample of 162 countries during 1999-2007. The empirical results suggest that higher FDI causes higher shadow economy and higher shadow economy causes higher FDI. The second objective is to answer whether the relationship between shadow economy and economic growth depends on the level of economic development. For this, the shadow economy Kuznets curve is employed using data of 162 countries during 1999-2007, and the dynamic panel system GMM is estimated. Considering the role of micro and small enterprises (MSEs), human and social capital, and multinational enterprises (MNEs) on shadow economy and based on unified growth theory, the empirical findings indicate that a cubic, N shape, functional form justifies the relationship between shadow economy and economic growth. Governments lose a large portion of their revenues through tax evasion, tax avoidance, and inefficient fiscal authorities or in sum shadow economy, which can contribute toward poverty reduction and promoting sustainable development. Therefore, the third objective of this study is to investigate the relationship between shadow economy and poverty by explaining the mechanism through which shadow economy affects poverty via its impact on government size and economic growth, and using the human poverty index (HPI) for developing and developed countries as an index of capability poverty. In order to achieve this objective, the three-way interaction model is utilized using data of 139 developing and 23 developed countries separately during 1999-2007. For developing countries the dynamic panel system GMM and for developed countries, the fixed and random effects method of estimation is used. The results suggest that increasing the shadow economy leads to increase poverty in developing countries while it decreases poverty in developed countries.